2017
DOI: 10.18203/2319-2003.ijbcp20174371
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reaction profile at psychiatry outpatient department of a tertiary care centre

Abstract: Background: Monitoring adverse drug reactions (ADRs) helps in alerting physicians and developing strategies to prevent and minimize the risk of developing ADRs. Data regarding pattern of ADRs due to psychotropic medications is scanty. Hence, the study was planned to assess ADRs among psychiatry outpatients of a tertiary care hospital in Maharashtra.Methods: A prospective, observational study was conducted in psychiatry outpatient department of a tertiary care centre for 3 months. Cases were enrolled by active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…In our study, an undesired effect occurred in 14 (15.9%) participants and this was higher than the study done in India and UAE, where 6.41% and 10.2% of the study participants, respectively, were reported to develop undesired effects. 11,12 In contrast, our finding was lower than two studies done in India, where the undesired effect rate was reported to be 20.4% and 43.5%, respectively. 13,14 The reason for the lower rate could be under documentation in medical records and/or the method of data collection as in the case of prospective and retrospective studies.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…In our study, an undesired effect occurred in 14 (15.9%) participants and this was higher than the study done in India and UAE, where 6.41% and 10.2% of the study participants, respectively, were reported to develop undesired effects. 11,12 In contrast, our finding was lower than two studies done in India, where the undesired effect rate was reported to be 20.4% and 43.5%, respectively. 13,14 The reason for the lower rate could be under documentation in medical records and/or the method of data collection as in the case of prospective and retrospective studies.…”
Section: Discussioncontrasting
confidence: 93%
“…10 DTPs are hence a major public health concern that could occur anywhere in the globe with no limit for a boundary. 11 Studies revealed that 5-10% of hospital admissions are associated with DTPs 12 and treatment adherence has also been used as one of the seven categories under DTPs that could affect patients proper drug therapy. 13…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation